Respuesta :
Answer:
see explanation
Step-by-step explanation:
Using the trigonometric identities
tan x = [tex]\frac{sinx}{cosx}[/tex] , sec x = [tex]\frac{1}{cosx}[/tex] , sin²x + cos²x = 1
Consider the left side
tan²y × cos²y + [tex]\frac{1}{sec^2y}[/tex]
= [tex]\frac{sin^2y}{cos^2y}[/tex] × cos²y + [tex]\frac{1}{\frac{1}{cos^2y} }[/tex] ← cancel cos²y in the product
= sin²y + cos²y
= 1
= right side ⇒ proven
Step-by-step explanation:
[tex] (\tan^2y) (\cos^2y) +\frac{1}{\sec^2y} = 1\\
LHS
= (\tan^2y) (\cos^2y) +\frac{1}{\sec^2y} \\\\
\frac{\sin^2y}{\cos^2y}\times \cos^2 y + \cos^2 y \\\\
= \sin^2y + \cos^2 y \\\\
= 1\\\\
= RHS\\\\
\purple {\boxed {\bold {\therefore (\tan^2y) (\cos^2y) +\frac{1}{\sec^2y} = 1}}} \\[/tex]
Hence Proved